2011
DOI: 10.3233/jad-2011-110209
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 Decreases Amyloid Pathology and Improves Behavior in a Transgenic Mouse Model of Alzheimer's Disease

Abstract: Increased oxidative stress is implicated in the pathogenesis of Alzheimer’s disease (AD). A large body of evidence suggests that mitochondrial dysfunction and increased reactive oxygen species occur prior to amyloid-β (Aβ) deposition. Coenzyme Q10 (CoQ10), a component of the mitochondrial electron transport chain, is well characterized as a neuroprotective antioxidant in animal models and human trials of Huntington’s disease and Parkinson’s disease, and reduces plaque burden in AβPP/PS1 mice. We now show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(80 citation statements)
references
References 81 publications
2
72
0
6
Order By: Relevance
“…It is also reported that pre-treatment with CoQ10 prevents Aβ accumulation; it can reduce the influx of extracellular Ca 2+ , and Ca 2+ release from mitochondria due to opening the mitochondrial transition pore after β-amyloid uptake [90]. CoQ10 treatment can also decrease plaque area and number in the hippocampus as well as in the cortex [91] which is in agreement with the results of the histopathological examinations obtained in the current study. It is of great importance to note that, histological examinations of brains of NF and PM groups showed no histo pathological alteration in the hippocampus as well as in the cortex.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It is also reported that pre-treatment with CoQ10 prevents Aβ accumulation; it can reduce the influx of extracellular Ca 2+ , and Ca 2+ release from mitochondria due to opening the mitochondrial transition pore after β-amyloid uptake [90]. CoQ10 treatment can also decrease plaque area and number in the hippocampus as well as in the cortex [91] which is in agreement with the results of the histopathological examinations obtained in the current study. It is of great importance to note that, histological examinations of brains of NF and PM groups showed no histo pathological alteration in the hippocampus as well as in the cortex.…”
Section: Discussionsupporting
confidence: 82%
“…It has been documented that CoQ10 acts as a powerful antioxidant and radical scavenger [26,27]. It can also help to regenerate other antioxidants, so it has been used as anti-aging and is effective in the improvement of cognitive disorders [28]. In the body, cells synthesize CoQ10 from the amino acid tyrosine, requiring adequate levels of vitamins such as folic acid [29].…”
Section: Introductionmentioning
confidence: 99%
“…CoQ10 treatment resulted in decreased plaque area and number in hippocampus and in overlying cortex immunostained with anA~42-specific antibody (46). Also recent data from clinical trials indicate that melatonin supplementation slows down the progression of cognitive impairment in AD patients.…”
Section: Future Directionsmentioning
confidence: 99%
“…CoQ10 was observed to reduce oxidative stress and tau pathology in mice (Dumont et al, 2011), and inhibited -amyloid ( A) formation (Ono et al, 2005). CoQ10 treatment has also been shown to decrease brain oxidative stress, reduce A plaque load, and improve cognitive performance in a transgenic mouse model of Alzheimer's disease (Dumont et al, 2011).…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%
“…CoQ10 was observed to reduce oxidative stress and tau pathology in mice (Dumont et al, 2011), and inhibited -amyloid ( A) formation (Ono et al, 2005). CoQ10 treatment has also been shown to decrease brain oxidative stress, reduce A plaque load, and improve cognitive performance in a transgenic mouse model of Alzheimer's disease (Dumont et al, 2011). In a recent study dietary supplementation of carnosine an endogenous peptide with metal chelating and free radical scavenging properties was observed to completely rescue AD and aging related mitochondrial dysfunction and was suggested as a potential candidate for a combined therapeutic approach for the treatment of AD (Corona et al, 2011).…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%